The Development and Evaluation of a Corpus-based Spanish Collocation Error Detection and Revision Suggestion Tool - Lu, Hui-Chuan (2019)
The topic of collocation has drawn attention for the past three decades in the lexical area of theoretical and applied linguistics. Our research team developed and evaluated a corpus-based assisted tool for collocation learning in Spanish. Based on the two constructed corpora (CEATE and CPEIC) and a Spanish collocation extraction tool (HCE), this computer-assisted learning tool, SpColEDRS, is easy to use to detect errors and also suggests revisions for Spanish collocations. Based on the evaluation, the research results indicated that the tool developed in this research can assist learners effectively, especially in the case of beginners. In addition, the results of the satisfaction survey provided positive confirmation of the effectiveness of this tool in assisting the learning of Spanish collocations. Finally, this study shed light on pedagogical applications of the constructed corpora and the learning of Spanish collocation with a corpus-based approach in a multilingual acquisition setting.